STRATEGI DALAM MENINGKATKAN KESADARAN MASYARAKAT MENUNAIKAN ZAKAT MAL DI BAZNAS KABUPATEN BARRU - Rizka Amaliah S; Nurfiah Anwar; Muhammad Nasri Khatman (Investama : Jurnal Ekonomi dan Bisnis, 2023)
Indonesia is a country with predominantly Muslim population. Indonesia's predominantly Muslim population has great potential in playing a role in realizing the social welfare of society and overcoming social problems. Zakat is a tool that can be used to overcome social problems so that public awareness is needed to pay zakat. However, until now public awareness of paying zakat is still low, especially zakat mal. As in the people of Barru Regency, a strategy is needed for the Barru Regency National Amil Zakat Agency as one of the zakat institutions sheltered by the Government in increasing public awareness of paying zakat mal at BAZNAS Barru Regency. This study aims to determine the level of public awareness in paying zakat mal, what are the strategies in increasing public awareness in fulfilling zakat mal at BAZNAS Barru Regency and to find out the inhibiting and supporting factors in implementing the strategy of BAZNAS Barru Regency. This type of research used is a qualitative method. The data analysis technique used is data reduction, data presentation, and conclusion/verification. The results of this study show that: 1) The level of public awareness in Barru Regency is still lacking in terms of the amount of zakat collected at BAZNAS Barru Regency which is far from the potential for zakat. 2) BAZNAS's strategy in increasing public awareness is by establishing UPZ, collaboration with third parties (ASN, Police, and KKDB), and direct or indirect outreach. 3) Inhibiting factors, namely public awareness of zakat is still relatively low, people who have the habit of channeling zakat directly to other people without going through institutions, lack of understanding about zakat in general, there are still muzakki who do not know that there is zakat other than zakat fitrah, namely zakat mal , People who are not aware of the consequences of zakat. Then the supporting factors for the implementation of the Barru Regency BAZNAS strategy are support from the government in the form of regional zakat regulations and appeals to regional heads, cooperation with government agencies and verticals and strong support from the Barru Regency Ulema Council